Strategy of Islamic Religious Education Teachers in Improving the Islamic Character of Students - Huda, M Sukri Afkharul; Sariman, Sariman; Khasanudin, Mohamad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
In the era of digitalization, education has a very important role, bringing changes in people's lives as well as bringing positive and negative effects. The negative impact of the emergence of a decrease in the moral behavior of students requires a genuinely effective educational strategy. This study uses a descriptive qualitative approach, which aims to describe and analyze the strategies of Islamic religious education teachers in improving Islamic character in Madrasah Tsanawiyah Siman Sekaran Lamongan, as primary data sources are the principal, vice-principal for curriculum, and teachers. The data collection techniques used participatory observation, unstructured interviews, and documentation. While the data analysis is used, data collection, condensation, presentation, and conclusion. The results of the strategy of Islamic religious education teachers in improving Islamic character at MTs Salafiyah Siman Sekaran are as follows: 1) Education strategies with habituation through prayer reading asmaul husna, istighosah and following congregational duhur prayers, and dhuha prayers 2) Educational strategies by good strategies or uswah can make students imitate or do good things that we teachers do, so we as teachers must already have good role models for students to emulate. 3) Educational strategies with advice through religious activities, Isra Mi'raj, Maulud Nabi, Nuzuul Quran, and flag ceremonies 4) Strategies by giving rewards to students will also foster competition in learning and achievement of both academic and non-academic achievements.